Motor Impairments, Striatal Degeneration, and Altered Dopamine-Glutamate Interplay in Mice Lacking PSD-95. (June 2014) - Zhang, Jingping; Saur, Taixiang; Duke, Angela N.; Grant, Seth G. N.; Platt, Donna M.; Rowlett, James K.; Isacson, Ole; Yao, Wei-Dong
Abstract Excessive activation of the N-methyl-d-aspartate (NMDA) receptor and the neurotransmitter dopamine (DA) mediate neurotoxicity and neurodegeneration under many neurological conditions, including Huntington's disease (HD), an autosomal dominant neurodegenerative disease characterized by the preferential loss of medium spiny projection neurons (MSNs) in the striatum. PSD-95 is a major scaffolding protein in the postsynaptic density (PSD) of dendritic spines, where a classical role for PSD-95 is to stabilize glutamate receptors at sites of synaptic transmission. Our recent studies indicate that PSD-95 also interacts with the D1 DA receptor localized in spines and negatively regulates spine D1 signaling. Moreover, PSD-95 forms ternary protein complexes with D1 and NMDA receptors, and plays a role in limiting the reciprocal potentiation between both receptors from being escalated. These studies suggest a neuroprotective role for PSD-95. Here we show that mice lacking PSD-95, resulting from genetic deletion of the GK domain of PSD-95 (PSD-95-ΔGK mice), sporadically develop progressive neurological impairments characterized by hypolocomotion, limb clasping, and loss of DARPP-32–positive MSNs. Electrophysiological experiments indicated that NMDA receptors in mutant MSNs were overactive, suggested by larger, NMDA receptor–mediated miniature excitatory postsynaptic currents (EPSCs) and higher ratios of NMDA- to AMPA-mediated corticostriatal synaptic transmission. In addition, NMDA receptor currents in mutant cortical neurons were more sensitive to potentiation by the D1 receptor agonist SKF81297. Finally, repeated administration of the psychostimulant cocaine at a dose regimen not producing overt toxicity-related phenotypes in normal mice reliably converted asymptomatic mutant mice to clasping symptomatic mice. These results support the hypothesis that deletion of PSD-95 in mutant mice produces concomitant overactivation of both D1 and NMDA receptors that makes neurons more susceptible to NMDA excitotoxicity, causing neuronal damage and neurological impairments. Understanding PSD-95–dependent neuroprotective mechanisms may help elucidate processes underlying neurodegeneration in HD and other neurological disorders.